Development of an Android-based Floor Gymnastic Application as an Alternative Teaching Material for PJOK Mix Learning at SD Negeri 113 Kota Jambi - Khairunnisa, Fitri; Wilyanti, Liza Septa; Kuntarto, Eko; Sofyan, Sofyan (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
This study aims to produce a product in the form of an android-based floor exercise application learning at SD Negeri 113 Jambi City. The background of the problem in this study is that some students at school are still not able to do good and correct basic gymnastic movements because some students still do not understand the correct steps of movement so that they experience obstacles in learning. This floor exercise application has been developed accurately, incorporating the latest movements, techniques, and practical, easy-to-use rules in learning. This research was conducted at Public Elementary School 113 with research subjects namely students of SD N 113 Jambi City. The research method used is the ADDIE model development research. The steps of this research start from analysis, design, development, implementation to evaluation. The results of the analysis of the research data show that the percentage score of the product trials carried out is 80% to 90% in the good category so that it can be concluded that this android-based floor gymnastics application product is suitable for use by students and teachers, especially sports.